The Effect of Implementing a Case Study-Based Problem Based Learning Model on Student Learning Outcomes at SMAN 2 Pulau Punjung - Samsul Anuar, Zafira Anuar (Department of Physics Universitas Negeri Padang, 2024)
This research was motivated by the low physics learning outcomes of students at SMA Negeri 2 Pulau Punjung. This is because in the learning process the teacher has not used a learning model that suits the characteristics of the material so that students are passive in following the learning process. The solution used to motivate and activate student learning in a pleasant learning atmosphere is to apply a case study-based problem based learning model. The type of research carried out was a quasi-experiment using a Randomized Possttest Only Control Group Design with sampling carried out using a census sampling technique (saturated sampling). Based on the results of the research and discussions that have been carried out, it can be concluded that there are differences in good physics learning outcomes for students in class done. From the conclusions above, we can obtain a significant difference in the use of a problem based learning model based on case studies on the physics learning outcomes of class XI Phase F students at SMA Negeri 2 Pulau Punjung for the 2023/2024 academic year.